The effects of recreational cannabis access on labor markets: Evidence from Colorado - Avinandan Chakraborty; Jacqueline Doremus; Sarah S. Stith (IZA Journal of Labor Economics, 2021)
Recreational cannabis markets possibly increase labor demand through investments in facilities for growing, processing, and retail sales of cannabis, as well as through other industries such as manufacturing, leisure, and hospitality. However, this increase in labor demand may vary substantially across counties within a state as most states with legal recreational cannabis allow individual counties to ban commercial cannabis sales. Meanwhile, labor supply may change through positive and negative effects from cannabis use. Using county-level Colorado data from 2011 to 2018 and exploiting variation across counties in the existence and timing of the start of dispensary sales, we test for changes in the unemployment rate, employment, and wages, overall and by industry subsector. Consistent with an increase in labor demand, we estimate that the sale of recreational cannabis through dispensaries is associated with a 0.7 percentage point decrease in the unemployment rate with no effect on the size of the labor force. We also find a 4.5% increase in the number of employees, with the strongest effects found in manufacturing. We find no effect on wages. Given the lack of a reduction in labor force participation or wages, negative effects on labor supply are likely limited, in line with the existing literature. The decrease in unemployment, coupled with an increase in the number of employees, indicates that labor demand effects likely dominate effects on labor supply. Our results suggest that policymakers considering recreational access to cannabis should anticipate a possible increase in employment.
Keywords: J21; R11; J3; K00; 330; cannabis; marijuana; labor demand; manufacturing